Morphometric study of the ghost crab Ocypode quadrata (Fabricius, 1887) (brachyura, ocypodidae) from Ubatuba, São Paulo, Brazil - Fransozo, A.; Negreiros-Fransozo, M. L.; Bertini, G. (Kluwer Academic/plenum Publ, 2002)
A morphometric study of the ghost crab Ocypode quadrata from Ubatuba, São Paulo, Brazil, focusing on the relationships between carapace width and carapace length, abdomen width, gonopod length and propodus length and height of the major cheliped is presented. An allometric positive growth was found for most of the analyzed relationships; however, important changes in the gonopod and abdomen were observed at the size at which sexual maturity is attained. Morphological (external) sexual maturity for both sexes is achieved at a smaller size than that at which gonad maturity is reached. Concerning heterochely, 53.3% of the analyzed specimens exhibited a longer propodus length in the right cheliped.